Preambule The “Dispute of the Greeks and Romans” (Libro de buen amor), interlocution, gesture, linguistic sign (Signifiances (Signifying), 2019)
This preamble lays down the terms of the debate, based on an “exemplary fable,” the “Dispute of the Greeks and Romans”, stanzas of a 14th century opus in verse among the most famous in Spanish literature, the Libro de Buen Amor. The episode  proves to be a perfect illustration of some important linguistic principles that are underexploited in the traditional analysis: “double contingency” or the ignorance by each of the interlocutors of what the sign means for the other; the signified as constructed ex post, resulting from the positioning of an outside observer; the double conception of the sign, as representation and as embodied action. The analysis of this edifying passage leads to an evocation of the different forms taken by the duplicity of the linguistic sign.